PENGENALAN BERETIKA KOMUNIKASI DIKALANGAN REMAJA PUTRI DI SMP SWASTA AMANAH TAHFIDZ QUR’AN DELI SERDANG - Butarbutar, Maria Haryanti; Lasmawanti, Sri; Lestari, Kartika Dwi (Nindikayla Institute, 2023)
Forms of communication and interaction between people have now developed following technological developments. There are still many teenagers who use social media without heeding the values ​​and norms and principles of decency. This community service activity aims to provide an understanding of the ethics of communicating through social media among adolescents. Therefore, we carry out community service to conduct